10- or 30-minute treadmill exercise rescues motor behaviors through inhibiting apoptosis in a rat MCAo model: Exercise rescues motor function via apoptosis in MCAo - Yoo, Jin; Kim, Daeyeol (Cellular and Molecular Biology, 2023)
Ischemic stroke, one of the world’s leading fatal diseases, has a high recurrence and incidence that can lead to severe mortality and disability. In this study, we investigated whether exercise can treat ischemic stroke to prevent recurrence and improve functional impairment. Experimental cerebral ischemia was induced by middle cerebral artery occlusion (MCAo) in rats, and the effect of 10- or 30-minute training for two weeks was evaluated. Following cylinder and rota-rod behavioral tests, we found that motor function was improved compared to the non-exercise group. In addition, the brain infarct volume was decreased after exercise following TTC staining. Further examination of the cell signaling mechanisms involved in the improvement showed that the immune reactivity significantly decreased the expression of the pro-apoptotic protein, Bax, and increased that of the anti-apoptotic protein, Bcl-2. Our results suggest that exercise has a beneficial effect on ischemic stroke for short- or long-term training.